Geomatic Tools for Water Management in a Community Irrigation System, Cruz del Eje, Córdoba. - Victoria Marinelli, M.; A. Mari, Nicolás; Marcelo Scavuzzo, C. (Journal of Agronomy Research, 2019)
An integral and efficient management of water for irrigation requires the adoption of new technologies to respond to the challenges imposed by the agricultural sector, in particular to stabilize production through the adequate use of water resources. In this sense, it is vital to characterize and know the amount of area which is under irrigation in such agricultural systems. In this paper we show the use of satellite information data in a GIS environment with the objective of characterizing the productive areas under irrigation in Cruz del Eje, Córdoba, Argentina in 3 types: A) irrigation region B) irrigable area and C) actually irrigated area. Multitemporal image indices and segmentation were used for this characterization and then maps of these 3 types of agricultural land cover were generated. Additionally, we present simple satellite images processing and classification procedures to increase the knowledge about the land cover over this irrigated area. Finally, we discuss how this geographically explicit information generated could be useful for the decision-making process on current irrigated areas and on the potential of productive systems through community irrigation systems.
Keywords: Random Forest; Multitemporal image indices; segmentation; NDVI; GIS; Argentina.